(untitled) (Zoo Botanica, 2025)
Plants produce secondary metabolites (SMs), which are bioactive compounds produced as an adaptive defence against herbivorous insect attacks. These compounds include alkaloids, terpenes, phenolics, and glucosinolates, which deter insects’ feeding, disrupt their digestive systems, and kill them. Insects have olfactory and gustatory receptors, which help them select or reject the plant hosts. Plant secondary metabolites (SMs) can either cause direct toxicity by acting as toxins for the insects or cause indirect toxicity by attracting parasitoids of pests. Plants use complex biosynthetic 3 pathways such as the shikimic acid pathway for phenolic and flavonoids, the Methylerythritol phosphate (MEP) and mevalonate pathway for terpenoids, and the acetate-malonate pathways for polyketide synthesis. These pathways are specifically regulated, upon tissue damage or stress, by plant hormones such as jasmonic acid and salicylic acid. Alkaloids such as nicotine and caffeine interfere with the insects’ nervous system, causing death. Azadirachtin, a terpenoid from neem, disrupts moulting and reproduction in insects, while tannins and flavonoids inhibit the digestive enzymes of insects. Although these compounds are plants’ natural defence, many insects of the families Nocutidae, Lepidoptera, Aphididae, Danainae, and Chrysomelidae have evolved certain molecular mechanisms, such as cytochrome P450 mono-oxygenase-based oxidation, sequestration, target insensitivity, and microbial symbiont-mediated detoxification, to protect themselves against SMs. This review discusses the biosynthesis of different plant SMs, their direct or indirect toxicity, and insects’ adaptations against these SMs, and Implications of SMs in modern research to explore their role as biopesticides.